Reusing Waste Ceramic and Waste Sanitary Ware in Concrete as Pozzolans with Nano-Silica and Metakaolin - Heidari, Ali; Tavakoli, Shiva; Tavakoli, Davoud (International Journal of Sustainable Construction Engineering and Technology, 2019)
Ceramic wastes are one of the largest waste materials among construction materials. Using waste materials in concrete is a good way to recycle them. This study works on the mechanical and durability properties of pozzolanic concrete containing ceramic tile and sanitary ware wastes as pozzolans incorporation metakaolin and nano-silica. This study was conducted in two parts: in the ï¬rst part, properties of concrete with different percentage of ceramic tiles and sanitary ware wastes as pozzolans was studied. In the second part, the simultaneous effect of ceramic wastes with nano-silica and metakaolin was studied. The results determined that using of different ceramic wastes as a pozzolan in concrete has negligible effect in mechanical properties and improves durability. Moreover, using waste ceramic powder with metakaolin and nano-silica simultaneously leads to improve mechanical properties and durability. Due to the reduction of cement consumption and the recycling of ceramic waste, it can be said that the use of ceramic waste in concrete is a step towards for sustainable development.